Historiography of Indonesian Culinary: Tracing Trails and National Identity Through the History of Food - Rohmawati, Yulia (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2024)
Indonesia's cultural heritage, especially its food traditions, needs more thorough documentation, making it hard to learn about the culture and national identity through cuisine. This often leads to cuisine being seen as just food, ignoring its deeper cultural and philosophical meanings. This study uses a historical approach to address this gap in understanding Indonesian culinary history. Various sources like photos, videos, documents, newspapers, and magazines are used as primary sources in this research. The research finds many historical cookbooks from colonial times to after Indonesia gained independence, each with unique features. These cookbooks reflect the cultural context of their time. Recognizing cuisine as a dynamic part of national identity, evolving over time and across regions, is crucial in establishing a national cuisine. This requires a deep dive into culinary history and an understanding of the role of Indonesian culinary historiography in shaping the nation's food culture.